2022
DOI: 10.3390/agronomy12123229
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response Curves of Pelargonic Acid against Summer and Winter Weeds in Central Italy

Abstract: Pelargonic acid is a non-selective post-emergence contact bio-herbicide which is registered both for cropping and non-cropping uses in several countries. Dose–response curves on the efficacy of pelargonic acid against common weeds in Mediterranean areas are not available. Dose–response curves of pelargonic acid efficacy against summer and winter annual weeds were evaluated in two field experiments (winter exp. in 2019 and summer exp. in 2020) in central Italy. Pelargonic acid was applied at five doses (1.4, 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…This weed recovery effect could also be due to the tested volume rate. In the present research, we used 500 L ha −1 , a higher water volume rate than Panacci et al [33], who obtained a PA response curve for several weeds using 300 L ha −1 , but lower than other authors, like Webber and Shrefler [30], who applied 935 L ha −1 obtaining good weed control.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…This weed recovery effect could also be due to the tested volume rate. In the present research, we used 500 L ha −1 , a higher water volume rate than Panacci et al [33], who obtained a PA response curve for several weeds using 300 L ha −1 , but lower than other authors, like Webber and Shrefler [30], who applied 935 L ha −1 obtaining good weed control.…”
Section: Discussionmentioning
confidence: 77%
“…Little field research has been conducted on the efficacy of natural herbicides for weed control, as the majority have studied pelargonic acid (PA) [11,[29][30][31][32][33]. To our knowledge, there are no reports of field research on the herbicidal activity of the natural products carvacrol (CAR), thymol (THY), eugenol (EUG), p-cymene (P-CYM), and citral (CIT).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of PA's potential as a bio-herbicide and its ability to contribute to the reduction of synthetic herbicides, researchers have been exploring its efficacy, and have shown that PA is the most successful bio-herbicide available (Webber et al, 2014a;Carroll et al, 2022;Muñoz et al, 2022;Pannacci et al, 2022). However, its effectiveness varies between weed species (Webber et al, 2014a;Webber et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%